Company Law - Koh, Alan K. (2023)
Singapore’s common law-origin corporate law regime ranks highly on corporate law and governance indices and is administered in part by superior courts served by judges with significant commercial expertise. As part of the Annual Review of Cases published by the Singapore Academy of Law (a multipartite institution representing private practitioners, lawyers in public service, the judiciary, and legal academia), this Paper reviews recent legally significant company law decisions of the Singapore superior courts (comprising the General Division of High Court, Appellate Division of the High Court, and the Court of Appeal) mostly decided in 2021. The cases reviewed feature a wide range of issues with domestic and international significance, including private enforcement and public regulation of directors’ duties, corporate veil piercing, reflective loss, dishonest assistance, and shareholder disputes. This Annual Review will be useful for academics and lawyers interested in jurisprudential developments in a leading Asian, common law jurisdiction, and on the diffusion and reception of landmark, foreign common law cases in a prominent Anglo-Commonwealth jurisdiction.